Demand-side management by electric utilities in Switzerland: Analyzing its impact on residential electricity demand - Nina Boogen; Souvik Datta; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
In this paper we use panel data from a survey conducted on 30 Swiss utilities to estimate the impact of demand-side management (DSM) activities on residential electricity demand using DSM spending and an energy efficiency score. Using the variation in DSM activities within utilities and across utilities over time we identify the impact of these programs and find that their presence reduce per customer residential electricity consumption by around 5%. If we consider monetary spending, the effect of a 10% increase in DSM spending causes around a 0.14% reduction in per customer residential electricity consumption. The cost of saving a kilowatt hour is around CHF 0.04 while the average cost of producing and distributing electricity in Switzerland is around CHF 0.18 per kilowatt hour. We conclude that current DSM practices in Switzerland have a statistically significant effect on reducing the demand for residential electricity.
Keywords: C33; C36; Q41; Q48; 330; Residential electricity; demand-side management; energy efficiency score; difference-in-differences; Switzerland; Lastmanagement; Elektrizitätswirtschaft; Elektrizität; Nachfrage; Energieeinsparung; Energiekonsum; Schweiz